Nilai-Nilai Spiritual yang Mencerminkan Budaya Organisasi Berdampak terhadap Peningkatan Kinerja Karyawan di Rumah Sakit YARSI - Irwan Kusnanda; Rokiah Kusumapradja (Jurnal Manajemen Kesehatan Indonesia, 2020)
Performance appraisal for employee usually based on the job description that has been designed by organization. Therefore, the result of employee’s performance appraisal will be considered based on employee’s capability to complete all the tasks from their job description. The objective of this research is to analyze and identify the effect of compensation benefit, organizational commitment and organizational culture towards employee’s performance in YARSI Hospital. The method of this research is using causality design method based on time dimension, one short study; the measurement towards dependent and independent variable at the same interval. The sampling technic in this research using Cluster random Sampling. Analyzed unit is data analysis using Regression. The result of this partial test revealed that employee’s performance affected to organizational commitment, compensation benefit, organizational culture and the result of this simultaneous test showed that the most significant effect is compensation benefit. Surprisingly, Researcher finds that in YARSI Hospital spread over the spiritual values proved that all employee remain working hard even though the compensation benefit system has not been implemented at the finest condition.